Erosion and Lateral Surface Processes. Issue 12 (14th December 2017) - Assouline, S.; Govers, G.; Nearing, M.A.
Abstract : Core Ideas: This special section is a snapshot of current work and understanding of lateral surface transport processes. The particular focus is on soil erosion. Soil erosion is a very large and very important topic. It must be addressed from both practical and rigorous scientific angles. Erosion can cause serious agricultural and environmental hazards. It can generate severe damage to the landscape, lead to significant loss of agricultural land and consequently to a reduction in agricultural productivity, induce surface water pollution due to the transport of sediments and suspended material to waterways and rivers, and alter the operation of hydraulic structures due to clogging of channels and sediment loading in reservoirs, estuaries, and oceans. The loss of soil due to erosion will also diminish its capacity to store water, which will not only negatively affect plant growth but might also increase the risk of flooding. Furthermore, erosion plays a significant role in the biogeochemical cycles of carbon, nitrogen, and phosphorus as it redistributes significant amounts of these elements across the surface of the Earth. This special section focuses on many of these aspects and gathers studies presenting valuable experimental and monitoring data, recent relevant technologies and measuring tools, and new modeling approaches that allow a better estimate of the intensity of the degradation processes and a better assessment of their multiscale nature and their coupling with biogeochemical processes as well as soil functioning.